Pengaruh Rasio Profitabilitas dan Solvabilitas terhadap Harga Saham dengan Market Valuation Ratio sebagai Variabel Moderasi - Fajriansyah, Bagus; Prihatni, Rida; Respati, Dwi Kismayanti (LPPM Universitas Negeri Jakarta, 2023)
The purpose of this research is to see the effect of Profitability Ratio and Solvency Ratio on Stock Price with Market Valuation Ratio as moderating variable. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. This study using purposive sampling method and produces 44 samples during the observation period. This study using the panel data analysis method which was processed using the IBM SPSS Statistics 26 application. The results show that the profitability ratio has a positive effect on stock price, the solvency ratio has no effect on stock price, the market valuation ratio has no effect on stock price, the market valuation ratio is unable to moderate the effect of profitability ratio on stock price, the market valuation ratio is unable to moderate the effect of solvency ratio on stock price.